2014
DOI: 10.1111/cen.12533
|View full text |Cite
|
Sign up to set email alerts
|

Chronic hypopituitarism is uncommon in survivors of aneurysmal subarachnoid haemorrhage

Abstract: Both anterior and posterior hypopituitarism are very uncommon following SAH and are not predicted by acute clinical, haemodynamic or endocrinological parameters. Routine neuroendocrine screening is not justified in SAH patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 31 publications
3
16
0
Order By: Relevance
“…Thus, the prevalence obtained from our analysis in the acute phase is higher compared to their results because we included endocrinal dysfunction in the very acute phase of aSAH (including \3 months). Many results from authors who studied both the acute and the chronic phase [10,18,20,44] confirm the improving trend of pituitary dysfunction with time. However, some authors [24,25] reported that new onset of hormone deficiency can occur in the follow up period as well.…”
Section: Prevalence Of Pituitary Dysfunctionmentioning
confidence: 73%
See 1 more Smart Citation
“…Thus, the prevalence obtained from our analysis in the acute phase is higher compared to their results because we included endocrinal dysfunction in the very acute phase of aSAH (including \3 months). Many results from authors who studied both the acute and the chronic phase [10,18,20,44] confirm the improving trend of pituitary dysfunction with time. However, some authors [24,25] reported that new onset of hormone deficiency can occur in the follow up period as well.…”
Section: Prevalence Of Pituitary Dysfunctionmentioning
confidence: 73%
“…Some are focused on the acute phase of aSAH [13,15], others on the chronic phase of aSAH [16,17], while some adress both [10,18]. There is substantial heterogeniety in the conclusions of these studies: although some suggest that hypopituitarism after aSAH affects only exceptional cases [19,20], others describe a high incidence reaching up to 50 % of cases [9,11,14]. Further, the clinical impact of any endocrine abnormalities that are present after aSAH remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
“…Several patients with Sheehan's syndrome have demonstrated acquired FVIII and vWF deficiency, thrombocytopenia, shorter PT and aPTT and higher FBG levels (111). The incidence of hypopituitarism after aneurysmal subarachnoid haemorrhage is unclear because of conflicting reports in the literature (112,113).…”
Section: Secondary Aimentioning
confidence: 99%
“…In a well-designed study by Gardner, using two different confirmatory tests for GHD adjusted for body mass index (BMI), 12% of patients had hypopituitarism at 12 months (88). GH deficiency is most common pituitary hormone deficiency reported after SAH (49,69,89). Pituitary hormone deficiencies after SAH recover in the majority of cases.…”
Section: Chronic Hypopituitarismmentioning
confidence: 99%
“…Pituitary hormone deficiencies after SAH recover in the majority of cases. For instance, in a prospective study of 100 SAH patients, 14% had acute glucocorticoid deficiency defined by inappropriately low plasma cortisol concentrations (89). However, only two of 41 (5%) had long-term ACTH deficiency and four of 41 (10%) had GHD when formally tested, with either insulin hypoglycaemia or, if contraindicated, glucagon or Synacthen testing, at a median of 15 months (89).…”
Section: Chronic Hypopituitarismmentioning
confidence: 99%